DIFFICULTIES IN TRANSLATING LEGAL TEXTS - Ziyada Amangeldievna, Djumanazarova (PT. Antis International Publisher, 2025)
Objective: This study investigates the challenges involved in the translation of legal texts, focusing on the impact of linguistic, cultural, and legal system differences on translation accuracy and effectiveness. Methods: A qualitative approach is employed to examine key difficulties such as terminological inconsistencies, syntactic complexity, and culturally specific legal concepts. The study also explores practical solutions, including terminological standardization, targeted translator training, and the integration of translation technologies. Results: The findings reveal that legal translators face significant barriers due to the interplay of legal traditions, language structures, and cultural context. The proposed strategies contribute to enhancing translation quality and consistency. Novelty: This article offers a comprehensive analysis of legal translation challenges and solutions, contributing to the broader discourse on professional practices in legal translation within multilingual legal environments.